Clinical research progress on eye scraping therapy for dry eye syndrome (眼部刮痧治疗干眼症的临床研究进展) - HE Yiqi (贺仪琦); LI Shanshan (李珊珊); YANG Jiangying (杨剑英); GENG Lina (耿丽娜) (中西医结合护理)
Dry eye is a common chronic ocular surface disease. The incidence rate of dry eye in China is younger and rising year by year. It has now become a national eye health issue. The triggering factors of dry eyes are closely related to the use of video terminals, aging, and environmental factors. Western medicine treatment mainly relies on artificial tears, local anti-inflammatory and immunosuppressive therapy, etc. It can achieve certain results in the short term, but it is prone to recurrence after stopping medication. Therefore, the urgent need for safe, effective, and minimally side effect treatments among patients is becoming increasingly prominent. This article found through the review of relevant literature on Traditional Chinese Medicine external treatment methods for dry eye that the appropriate techniques of Traditional Chinese Medicine have attracted much attention due to their characteristics of "simplicity, convenience, affordability, and effectiveness". Among them, eye scraping therapy stimulates the meridians and acupoints around the eyes, regulates local Qi and blood circulation, and shows unique potential in improving dry eye symptoms. It has significant effects in practical clinical treatment and is worthy of further promotion and research. (干眼是一种常见的慢性眼表疾病, 其发病率在我国呈年轻化且逐年上升趋势, 已成为影响国民眼健康的重要问题。干眼的诱发因素与视频终端的频繁使用、人口老龄化以及环境因素等密切相关。中医适宜技术因其“简、便、廉、验”的特点, 在干眼治疗领域备受关注。眼部刮痧作为一种重要的中医特色适宜技术, 在改善干眼症状方面展现出独特潜力。本研究就眼部刮痧治疗干眼症的作用机制及临床研究进展进行系统综述, 旨在为临床治疗提供有益的参考和借鉴。)